A High Frame Rate Analog Front-End IC With Piezoelectric Micromachined Ultrasound Transducers Using Analog Multi-Line Acquisition for Ultrasound Imaging Systems - Ji-Yong Jeong; Jong-Keun Song; Min-Seog Choi; Seong-Kwan Hong; Oh-Kyong Kwon (IEEE Access, 2021)
This paper proposes a high frame rate analog front-end (AFE) IC combined with a piezoelectric micromachined ultrasonic transducer (PMUT) for ultrasound imaging systems (UISs). The proposed AFE IC, which consists of 8-channel transceivers and a peripheral circuit, employs analog multi-line acquisition (AMLA) based on sub-array beamforming. This AMLA generates multiple scanlines during a scan time by simultaneously and precisely controlling the delay of the AFE IC, thus achieving the high frame rate of the AFE IC. The sensitivities of the PMUT for transmitting and receiving ultrasound waves are simulated to be 67.5 kPa/V and 1.2 mV/kPa, respectively, which are high enough to mitigate the needs of the high-voltage electronics for UISs. The proposed AFE IC was fabricated using a 0.18- $μ \text{m}$ silicon-on-insulator process and occupies an active area of 2.56 mm $×1.68$ mm. The measurement results using the simulated PMUT parameters show that the proposed AFE IC with the AMLA precisely controls its delay up to $1~μ \text{s}$ at a clock frequency of 40 MHz. It also acquires more than 9,000 scan/s even at a focal depth of 150 mm, which is at least twice greater than those of prior works, achieving a high frame rate of 93 Hz when 100 scanlines are used for a frame. In addition, a figure-of-merit, which considers the energy consumption per channel/scan and the energy loss, is achieved to be 20 nJ/scan/dB at a focal depth of 150 mm and a center frequency of 3.6 MHz; this is the best result compared to previously reported works. Therefore, the proposed AFE IC is suitable for UISs requiring a high frame rate.